Gemstones contextualised and applied : mindful fashion practice : a thesis presented in partial fulfilment of the requirements for a Master in Design at Massey University, Wellington, New Zealand - Louw, Johani (Massey University, 2021)
We are living in a time where people are growing more disconnected – from each other and themselves. This disconnect has led to emotional and mental distress, which people attempt to avoid addressing through unsustainable systems and practices in which they seek short-term, instant pleasures. With this practice-based design research, I am creating a wardrobe that enables the wearer to guide and express their emotional well-being by incorporating crystals as an integral part of fashion design. I aim to design clothing that allows the wearer to feel confident to evoke particular states of mind and, through their clothing, spark a conversation with others about their emotionality. Through secondary research, this project is guided by looking at crystal rituals, using a ‘Positive Design’ framework, and the agency of objects. These are in some way applied to and considered through every designed element. These designs investigate crystals as tools of healing through the use of print, and fabric manipulation, and embroidery, particularly its visual and textural form within the garment and meaningful location in relation to the body. Alongside this, textile print design is used to realise the relationship between the crystals and their corresponding chakras. With the designs based around chakra systems and the effective properties of crystals, the wearer is encouraged to reflect on their emotional well-being and use the clothing as a tool to help guide their mentality on any given day. By creating clothing that promotes internal reflection and works toward emotional well-being, the fashion system can be reimagined as a tool to evoke desired feelings. This design practise encourages mindful dressing and conversations of emotionality between the wearer, viewer and maker.
Figures 1 & 2 are © Bloomsbury Publishing Plc 2022 and have been removed but may be accessed via the link in the caption. Figure 6 is licensed for re-use under a Creative Commons Attribution-NonCommercial-NoDerivs 2.5 License.
Keywords: 330315 Textile and fashion design